Lightweight masonry block from oil palm kernel shell - Agus Muntohar, Muhammad Ekhlasur Rahman (ELSEVIER, 2014)
A large amount of waste produced in the processing of palm oil is one of the main contributors to the environmental problem. This paper presents an experimental study on the development of the shellcrete masonry block that made of oil palm kernel. The study was focused on the physical, compressive strength and flexural strength of shellcrete. The eco-efficiency of the shellcrete was also evaluated by measuring the carbon footprint. The shellcrete was made by mixing the Portland cement (PC), sand, and oil palm kernel shell (PKS). A control specimen made of PC and sand mixture (sandcrete) was also prepared. The specimen size was 220 mm length, 110 mm width and 80 mm in thickness. The maximum strength obtained was 22 MPa by mixing proportion of 1 PC:1 Sand:1 PKS, but the recommended mix proportion of the shellcrete for building materials was 1 PC:1 Sand:2 PKS as an optimum mix design for eco-friendly shellcrete.